2011
DOI: 10.1177/1071181311551241
|View full text |Cite
|
Sign up to set email alerts
|

Auditory-Visual Redundancy in Vehicle Control Interruptions: Two Meta-analyses

Abstract: Two novel versions of a meta analysis were employed to assess the conditions of ongoing vehicle control task simulations in which (1) auditory presentation of an interrupting task were beneficial over visual presentations and (2) redundant (av) presentation was better than single modality presentation (providing redundancy gain). Altogether 29 studies were identified. The results revealed that the interrupting task benefited from auditory presentation, but the ongoing task (visual vehicle control task) general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 6 publications
(10 reference statements)
0
26
0
Order By: Relevance
“…These reviews are reported individually (Lu et al, 2011;Wickens et al, 2011). In summary, these reviews compared operator performance in an on-going visual/manual task context (e.g., flying, driving, tracking).…”
Section: Meta-analyses: Empirical Performance Datamentioning
confidence: 96%
“…These reviews are reported individually (Lu et al, 2011;Wickens et al, 2011). In summary, these reviews compared operator performance in an on-going visual/manual task context (e.g., flying, driving, tracking).…”
Section: Meta-analyses: Empirical Performance Datamentioning
confidence: 96%
“…The absence of redundancy gains in these studies may be explained by the following three factors: (1) redundant information presentation can require more processing time, (2) the auditory component of visualauditory pairings may divert attention away from an ongoing task, and (3) the contents of two messages that are presented in different channels may not be synchronized in time, and hence be difficult to fuse (Wickens et al, 2011). Overall, redundancy gains or costs appear to depend on the details of the experimental setup and the variables that were manipulated in each study.…”
Section: Introductionmentioning
confidence: 93%
“…The visual advantage could have resulted from the affordance of reviewability -the operator can use vision to quickly scan the forgotten information especially when the length of message is challenging working memory (Wickens, Goh, Helleberg, Horrey, & Talleur, 2003;Wickens & Gosney, 2003). In two recent studies, Wickens and colleagues (Lu et al, 2013;Wickens, Prinet, Hutchins, Sarter, & Sebok, 2011) conducted meta-analyses of 68 and 29 studies on task performance as a function of interrupting task modality. The two studies showed that the communication accuracy of the interrupting tasks (which is of interest for the dissertation) enjoyed a significant redundancy gain against the best single modality component (almost always auditory).…”
Section: Technology Mediated Communicationmentioning
confidence: 99%
“…With a medium supporting high level of reviewability, like text, handover participants can easily refer back and forth to any information during a handover. It supports conversational context and allows handoff participants to allocate more cognitive resources to interpret and synthesize information being handed over Lu et al, 2013;Wickens et al, 2011).…”
Section: Effect Of Reviewability On Handover Perception and Comprehenmentioning
confidence: 99%
See 1 more Smart Citation